Advances in CAR design. Issue 3 (September 2021) - Heard, Amanda; Chang, Jufang; Warrington, John M.; Singh, Nathan
Abstract: Chimeric antigen receptor (CAR) T cells have revolutionized the management of B cell malignancies. These synthetic molecules are composed of peptide fragments from several distinct immune cell proteins and link highly-specific antigen recognition with potent T cell activation. Despite impressive results in many, less than half of patients treated will achieve durable remission after CAR therapy. Recent studies have identified the central role that each structural component of the CAR molecule plays in regulating T cell function. Significant effort has been dedicated to exploring strategies to improve the design of CARs themselves or integrate their activity with other regulatory circuits to enable more precise function. In this review, we will summarize recent pre-clinical and clinical studies that have evaluated novel CAR design formats. Highlights: Current approved CAR-based T cell therapies target either CD19 or BCMA, are second-generation in their design and employ either CD28 or 41BB co-stimulatory domains The divergent T cell biology driven by these two co-stimulatory domains remains poorly understood and warrants investigation to inform clinical decisions and novel design Exploration of other co-stimulatory domains will further enable more nuanced design of T cells with more tailored effector function CAR sub-units not directly involved in antigen-engagement or signaling can also significantly regulate T cell function, and should be evaluated in detail in design of new CARs Many innovative strategies that enable more selective T cell activation or inducible enhancement of T cell function are currently under exploration. The coming years will certainly see more innovation in this area as synthetic biology and genome engineering become more facile.